New insights into the phenotype of human dendritic cell populations. Issue 1 (29th January 2016) - Clark, Georgina Jane; Kupresanin, Fiona; Fromm, Phillip Dieter; Ju, Xinsheng; Muusers, Leticia; Silveira, Pablo Alejandro; Elgundi, Zehra; Gasiorowski, Robin Edward; Papadimitrious, Michael Stefan; Bryant, Christian; Lee, Kenneth Maan Liong; Clarke, Candice Jane; et al.
Abstract : HLDA10 is the Tenth Human Leukocyte Differentiation Antigen (HLDA) Workshop. The HLDA Workshops provide a mechanism to allocate cluster of differentiation (CD) nomenclature by engaging in interlaboratory studies. As the host laboratory, we invited researchers from national and international academic and commercial institutions to submit monoclonal antibodies (mAbs) to human leukocyte surface membrane molecules, particularly those that recognised molecules on human myeloid cell populations and dendritic cells (DCs). These mAbs were tested for activity and then distributed as a blinded panel to 15 international laboratories to test on different leukocyte populations. These populations included blood DCs, skin‐derived DCs, tonsil leukocytes, monocyte‐derived DCs, CD34‐derived DCs, macrophage populations and diagnostic acute myeloid leukaemia and lymphoma samples. Each laboratory was provided with enough mAb to perform five repeat experiments. Here, we summarise the reactivity of different mAb to 68 different cell‐surface molecules expressed by human myeloid and DC populations. Submitted mAbs to some of the molecules were further validated to collate data required to designate a formal CD number. This collaborative process provides the broader scientific community with an invaluable data set validating mAbs to leukocyte‐surface molecules. Monoclonal antibodies: Sharing to accelerate research: International laboratories have collaborated to assess the activity and clinical potential of a wide range of monoclonal antibodies. Monoclonal antibodies—pure preparations of antibodies derived from a single cell clone—are widely used for clinical research, diagnosis and therapy. Georgina Clark and colleagues at the ANZAC Research Institute in Concord, Australia, used their hosting of the recent Human Leucocyte Differentiation Antigen (HLDA10) Workshop to combine the expertise of antibody research groups from around the world. With a 3‐decade history, the nomenclature conventions that have resulted from the HLDA workshops are particularly important. Monoclonal antibodies that recognize key cells of the immune system, particularly those known as dendritic cells, were submitted by many institutions and independently assessed by 15 international laboratories. This collaboration breaks down barriers that often inhibit the sharing of data and expertise, and provides an invaluable open database to accelerate the use of antibodies to fight disease.